Flash Education

Generic selectors
Exact matches only
Search in title
Search in content
Post Type Selectors
post
question

Chapter – 1 : Quadratic Equations With One Variable | Chapter Solution Class 10

Quadratic Equation
WhatsApp
Book Name : Ganit Prakash
Subject : Mathematics
Class : 10 (Madhyamik)
Publisher : Prof Nabanita Chatterjee
Chapter Name : Quadratic Equations With One Variable (1st Chapter)

Application 1

I see whether the following equations can be written in the form of ax2 + bx + c = 0, Where a, b, c are real numbers and a ≠ 0.

(iv) (x – 2)2 = x3 – 4x + 4

Solution

(x – 2)2 = x3 – 4x + 4

or, x2 – 4x + 4 = x3 – 4x + 4

or, x2 – x3 = 0

This is not a quadratic equation, as it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

(v) (x – 3)3 = 2x(x2 – 1)

Solution:

x3 – 9x2 + 27x + 27 = 2x3 – 2x

or, x3 – 2x3 – 9x2 + 27x + 2x + 27 = 0

or, -x3 – 9x2 + 29x + 27 = 0

This is not a quadratic equation, as it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

Application 4

The length of a rectangular area is 2 m more than its breadth and its area is 24 sqm. I construct a quadratic equation in one variable. [Let me do it myself]

Solution:

Let the breadth of the rectangle = x m

the length of the rectangle = (x + 2) m

According to the given problem,

(x + 2)x = 24

or, x2 + 2x – 24 = 0

Here, co-efficient 0f x2 = 1, co-efficient 0f x = 2 and co-efficient 0f xo = -24

Let us workout – 1.1

Question 1

I write the quadratic polynomials from the following polynomials by understanding them.

Question (i)

x2 – 7x + 2 

Solution:

This is a quadratic equation.

Reason:

As it is in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

Question (ii)

7x3 – x(x+2)

Solution:

7x3 – x2 – 2x

This is not a quadratic equation.

Reason:

As it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

Question (iii)

2x(x+5) + 1

Solution:

2x2 + 10x + 1

This is a quadratic equation.

Reason:

As it is in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

Question (iv)

2x – 1

Solution:

2x – 1

This is not a quadratic equation.

Reason:

As it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

Question 2

Which of the following equations can be written in the form of ax2 + bx + c = 0, where a, b, c are real numbers and a ≠ 0? Let us write it.

(i) x – 1 + 1/x = 6, (x ≠ 0)

Solution:

x2-x+1x=6

or, x2 – x + 1 = 6x

or, x2 – x – 6x + 1 = 0

or, x2 – 7x + 1 = 0

This is a quadratic equation. As it is in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

(ii) x + 3/x = x2

Solution:

x2+3x=x2

or, x2 + 3 = x3

or, x3 – x2 – 3 = 0

This is not a quadratic equation. As it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

(iii) x2 – 6√x + 2 = 0

Solution:

This is not a quadratic equation. As it is not in the form ax2 + bx + c = 0 [where a, b, c are real numbers and a ≠ 0]

(iv) (x – 2)2 = x2 – 4x + 4

Solution:

This is not a quadratic equation.

Question 3

Let us determine the power of the variable for which the equation x6 – x3 – 2 = 0 will become a quadratic equation.

Solution:

x6 – x3 – 2 = 0

or, (x3)2 – x3 – 2 = 0

This is a quadratic equation with respect to x3 .

Question 4 (i) 

Let us determine the value of ‘a’ for which the equation (a – 2)x2 + 3x + 5 = 0 will not be a quadratic equation.

Solution:

(a – 2)x2 + 3x + 5 = 0

If the value of a = 2, it will be 0x2 + 3x + 5 = 0

or, 3x + 5 = 0

So, if the value of a = 2, it will not be a quadratic equation.

Question 4 (ii) 

If x/(4 – x) = 1/3x, (x ≠ 0, x ≠ 4) be expressed in the form of ax2 + bx + c = 0 (a ≠ 0), then let us determine the coefficient of x.

Solution:

x4-x=13x x4-x-13x=0 3×2-(4-x)(4-x)3x=0

or, 3x2 – 4 + x = 0

or, 3x2 + x – 4 = 0

This is in the form of ax2 + bx + c = 0 and the coefficient of x is 1.

Question 4 (iii) 

Let us express 3x2 + 7x + 23 = (x + 4)(x + 3) + 2 in the form of the quadratic equation ax2 + bx + c = 0 (a ≠ 0).

Solution:

3x2 + 7x + 23 = (x + 4)(x + 3) + 2

or, 3x2 + 7x + 23 = x2 + 7x + 12 + 2

or, 3x2 = 7x – 7x + 23 – 14 – x2 = 0

or, 2x2 + 0.x + 9 = 0

Question 4 (iv) 

Let us express the equation (x + 2)3 = x(x2 – 1) in the form of ax2 + bx + c = 0 (a ≠ 0) and write the co-efficient of x2, x and xo.

Solution:

(x + 2)3 = x(x2 – 1)

or, x3 + 6x2 + 12x + 8 = x3 – x

or, x3 – x3 + 6x2 + 12x + x + 8 = 0

or, 6x2 + 13x + 8 = 0

∴ co-efficient of x2 is 6,

co-efficient of x is 13,

co-efficient of xo is 8.

Question 5

Let us construct quadratic equations in one variable from the following statement.

Question 5 (i)

Divide 42 into two parts such that one part is equal to the square of the other part.

Solution:

Let one part is x and the other part is 42 – x.

According to question

x2 = 42 – x

or, x2 +  x – 42 = 0

Question 5 (ii)

The product of two consecutive positive odd numbers is 143.

Solution:

Let one positive odd number is 2x – 1 and the next odd number is 2x + 1.

∴ (2x – 1)(2x + 1) = 143

or, 4x2 – 1 = 143

or, 4x2 – 1 – 143 = 0

or, 4x2 – 144 = 0

or, 4(x2 – 36) = 0

or, (x2 – 36) = 0

Question 5 (iii)

The sum of the squares of two consecutive numbers is 313.

Solution:

let one number be x and the other number is x + 1.

According to Question

x2 + (x + 1)2 = 313

or, x2 + x2 + 2x + 1 = 313

or, 2x2 + 2x – 312 = 0

∴ x2 + x – 156 = 0

Question

Let us construct the quadratic equations in one variable from the following statements.

Question 6 (i)

The length of the diagonal of a rectangular area is 15 m and the length exceeds its breadth by 3 m.

Solution:

Let the breadth and the length of the rectangle are ‘x’ m. and (x + 3) m respectively.

According to the given problem,

x2 + (x + 3)2 = 152

or, x2 + x2 + 6x + 9 = 225

or, 2x2 + 6x – 216 = 0

or, 2(x2 + 3x – 108) = 0

or, x2 + 3x – 108 = 0

Question 6 (ii)

One person bought some kg of sugar in Rs 80. If he would get 4 kg more sugar with that money, then the price of 1 kg sugar would be less by Rs 1.

Solution:

Let the price of x kg sugar is Rs 80

∴ The price of 1 kg of sugar is 80/x

According to the given problem,

Flash Education

or, 80 – x + 320/x – 4 – 80 = 0

or, -x2 + 320 – 4x = 0

∴ x2 + 4x -320 = 0 is the required equation.

Question 6 (iii)

The distance between the two stations is 300 km. A train went to the second station from the first station with uniform velocity. If the velocity of the train is 5 km/hour more, then the time taken by the train to reach the second station would be lesser by 2 hours.

Solution:

Let the speed of the train is ‘x’ km/hr

∴ To go 300 km the train takes 300/x hr

If the speed of the train is (x + 5) km/hr, the time required will 300/(x + 5) hr.

According to the problem,

Flash education 1

or, 300x + 1500 – 300 x = 2(x2 + 5x)

or, 1500 = 2(x2 + 5x)

or, 2(x2 + 5x) = 1500

or, x2 + 5x = 750

or, x2 + 5x – 750 = 0

∴ x2 + 5x – 750 = 0  is the required equation.

Question 6 (iv)

A clock seller sold a clock by purchasing it at Rs. 336. The amount of his profit percentage is as much as the amount with which he bought the clock.

Solution:

Let the cost price of the watch is Rs. x.

∴ Profit = x% of x

= x×x100

= x2/100

According to the problem,

x+x2/00=336

or, 100x + x2 = 33600

or, x2 + 100x – 33600 = 0

∴ x2 + 100x – 33600 = 0 is the required equation.

Question 6 (v)

If the velocity of the stream is 2 km/hr, then the time taken by Ratanmajhi to cover the 21 km downstream and upstream is 10 hours.

Solution:

Let the speed of the boat in still water is x km/hr.

∴ The speed of the boat with the current is (x + 2) km/hr and the speed of the boat against the current is (x-2) km/hr.

According to the problem,

Flash Education 3

or, 21x – 42 + 21x + 42 = 10 (x + 2)(x – 2)

or, 42x = 10(x2 – 4)

or, 5(x2 – 4) = 21x

or, 5x2 – 20 – 21x = 0

∴ 5x2 – 21x – 20 = 0 is the required equation.

Question 6 (vi)

The time taken to clean out a garden by Majid is 3 hours more than Mahim. Both of them together can complete the work in 2 hours.

Solution:

Let Mahim alone takes x hrs. to finish the work & Majid alone take (x + 3) hrs to finish the work.

According to the problem,

Flash Education 4

or, 4x + 6 = x2 + 3x

or, x2 + 3x = 4x + 6

or, x2 + 3x – 4x – 6 = 0

or, x2 – x – 6 = 0

∴ x2 – x – 6 = 0 is the required equation.

Question 6 (vii)

The unit digit of a two-digit number exceeds its ten’s digit by 6 and the product of two digits is less by 12 from the number.

Solution:

Let in a two digit number, the digit in the tenth place is x and the digit in the unit place is (x+6).

∴ The number is 10x + (x+6).

According the given problem, x(x+6) + 12 = 10x + x + 6

or, x2 + 6x + 12 = 11x+6

or, x2 – 5x + 6 = 0 is the required equation.

Question 6 (viii)

There is a road of equal width around the outside of a rectangular playground having a length of 45 m. and breadth of 40 m and the area of the road is 450 sq.m.

Solution:

Let the width of the path = ‘x’ m.

According to the problem,

(45+ 2x) × (40 + 2x) – 45 × 40 = 450

or, 1800 + 90x + 80x + 4x2 – 1800 = 450

or, 4x2 + 170x – 450 = 0

or, 2x2 + 85x – 225 = 0 is the required equation.

Application 8

Let me write by calculating, for what value of k, 1 will be a root of the quadratic equation x2 + kx + 3 = 0 [Let me do it myself].

Solution:

As one root of equation x2 + kx + 3 = 0 is 1.

∴ 12+ k. 1+3=0

or, 1+k+3=0

or k+ 4 = 0

∴ k = -4.

Application 13

I solve and write the two roots of the quadratic equation a/(ax – 1) + b/(bx – 1) = a + b [Let me do it myself]

Solution:

Flash Education 7

or, (2a – a2x)(bx – 1) + (2b – b2x)(ax – 1) = 0

or, 2abx – a2bx2 – 2a + a2x +2abx – ab2x2 – 2b + b2x = 0

or, – a2bx2 – ab2x2 + 2abx + a2x + 2abx + b2x – (2a + 2b) = 0

or, – (a2b + ab2)x + (a2 + b2 + 4ab)x – (2a + 2b) = 0

or, (a2b + ab2)x – {(a + b)2 + 2ab}x + 2(a + b) = 0

or, ab (a + b)x2 – (a + b)2x – 2abx + 2(a + b) = 0

or, x(a + b){abx – (a+b)} – 2{abx – (a+b)}=0

or, {abx – (a+b)} {x(a+b) – 2} = 0

Either (a + b)x – 2 = 0

∴ x = 2/(a+b)

or, abx – (a + b) = 0

∴ x = (a+b)/ab

Application 15

I solve the quadratic equation (x + 3)/(x – 3) + (x – 3)/(x + 3) = 2½ (x ≠ -3, 3) [Let do it myself]

Solution:

Flash Education 8

or, (x2 + 6x + 9 + x2 – 6x + 9) × 2 = 5 × (x2 – 9)

or, 4x2 + 36 = 5x2 – 45

or, 5x2 – 4x2 – 45 – 36 = 0

or, x2 – 92 = 0

or, (x + 9)(x – 9) = 0

Either, x + 9 = 0  ∴ x = – 9

or, x – 9 = 0  ∴ x = 9

Let us workout – 1.2

Question 

1. In each of the following cases, let us justify and write whether the given values are the roots of the given quadratic equation :

Question 1 (i)

x2 + x + 1 = 0; 1, -1

Solution:

When x = 1

(1)2 + 1 + 1 = 3

When x = – 1

(-1)2 – 1 + 1 = 1

∴ 1 and -1 are not the roots of the given equation.

Question 1 (ii)

8x2 + 7x = 0, 0, – 2

Solution:

When x = 0

∴ 8(0)2 + 7(0) = 0

When x = – 2

∴ 8(-2)2 + 7(-2) = 32 – 14 = 18

∴ 0 is the root while -2 is not the root of the given equation.

Question 1 (iii)

x + 1/x = 13/6

Solution:

When x = 5/6

∴ Flash Education 9

When x = 4/3

∴ Flash Education 10

∴ 5/6 and 4/3 are not the roots of the given equation.

Question 1 (iv)

x2 – √3 x – 6 = 0

Solution:

When x = – √3

∴ (- √3)2 – √3 (- √3) – 6

= 3 + 3 – 6

= 0

When x = 2√3

∴ (2√3)2 – √3 (2√3) – 6

= 12 – 6 – 6

= 0

∴ (- √3) and (2√3) are the roots of the given equation.

Question 2 (i)

Let us calculate and write the value of k for which 2/3 will be a root the quadratic equation 7x2 + kx – 3 = 0

Solution:

7x2 + kx – 3 = 0

As 2/3 is one root of the equation 7x2 + kx – 3 = 0

∴ 7(2/3)2 + k (2/3) – 3 = 0

or, 7 (4/9) + 2k/3 – 3 = 0

or, 28/9 + 2k/3 – 3 = 0

or, 2k/3 = 3 – 28/9

or, 2k/3 = -1/9

∴ k = – 1/6

Question 2 (ii)

Let us calculate and write the value of k for which -a will be a root of the quadratic equation x2 + 3ax + k = 0.

Solution:

x2 + 3ax + k = 0

As (-a) is the root of the equation

∴ x2 + 3ax + k = 0

(-a)2 + 3a(-a) + k = 0

a2 – 3a2 + k = 0

-2a2 + k = 0

∴ k = 2a2

Question 3

If 2/3 and -3 are the two roots of the quadratic equation ax2 + 7x + b = 0, then let me calculate the values of a and b.

Solution:

When x = 2/3

∴ a(2/3)2 + 7(2/3) + b = 0

or, 4a/9 + 14/3 + b = 0

or, (4a + 42 + 9b)/9 = 0

or, 4a + 9b = -42 —– (i)

When x = -3

a(-3)2 + 7 (-3) + b = 0

9a-21 + b = 0

9a + b = 21 —– (ii)

Now, solving 4a+ 9b = 42 and 9a + b = 21,

we get, a = 3 & b = – 6

Question

Let us solve

Question 4 (i) 

3y2 – 20 = 160 – 2y2

Solution:

3y2 – 20 = 160 – 2y2

or, 3y2+ 2y2 = 160 + 20

or, 5y2 = 180

or, 5y2 – 180 = 0

or, 5(y2 – 36) = 0

or, y2 – 36 = 0

or, (y + 6) (y – 6) = 0

∴ When y + 6 = 0 ⇒ y = – 6

and when y 6 = 0 ⇒ y = 6

Question 4 (ii)

(2x+1)2 + (x + 1)2 = 6x + 47

Solution:

(2x + 1)2 + (x + 1)2 = 6x + 47

or, 4x2 + 4x + 1 + x2 + 2x + 1 – 6x – 47 = 0

or, 5x2 – 45 = 0

or, 5(x2-9) = 0

(x)2– (3)2 = 0

(x + 3) (x-3)= 0

∴ Either x + 3 = 0 ⇒ x = -3

Or, x – 3=0 ⇒ x = 3

Question 4 (iii)

(x-7) (x-9) = 195

Solution:

(x-7) (x-9) = 195

or, x2 – 7x – 9x+ 63 – 195 = 0

or, x2 – 16x – 132 = 0

or,  x2 – 22x + 6x – 132 = 0

or, x(x-22)+6 (x-22) = 0

=> (x – 22) (x+6) = 0

Either x – 22 = 0 ⇒ x = 22

or, x + 6 = 0 ⇒ x = – 6

Question 4 (iv)

3x – 24/x = x/3, x ≠ 0

Solution:

3x – 24/x = x/3

or, (3x2 – 24)/x = x/3

or, (3x2-24) × 3 = x2

or, 9x2 – 72 – x2 = 0

or, 8x2 – 72 = 0

or, 8(x2-9) = 0

or, (x2 – 9) = 0

or, (x)2 – (3)2 = 0

(x + 3) (x-3)= 0

Either x + 3 = 0 ⇒ x = -3

Or, x – 3 = 0 ⇒ x = 3

Question 4 (v)

x/3 + 3/x = 15/x, x ≠ 0

Solution:

x/3 + 3/x = 15/x

or, (x2 + 9)/3x = 15/x

or, x2 + 9 = 45

or, x2 -36 = 0

or, (x + 6) (x-6)= 0

∴ x = 6 and – 6

Question 4 (vi)

10x – 1/x = 3, x ≠ 0

Solution:

10x – 1/x = 3

or, (10x2 – 1)/x = 3

or, 10x2 – 1 = 3x

or, 10x2 – 3x – 1 =0

or, 10x2 – 5x + 2x – 1 = 0

or, 5x(2x – 1) + 1(2x – 1)= 0

or, (2x – 1) (5x + 1) = 0

Either, 2x – 1 = 0 ⇒ x = 1/2

or, 5x + 1 = 0 ⇒ x = -1/5

 

Let us work out 1.5

Question 1

Let us write the nature of two roots of the following quadratic equations :

(i) 2x² + 7x + 3 = 0

(ii) 3x² – 2√6 x + 2 = 0

(iii) 2x² – 7x + 9 = 0

(iv) 5/3 x² – 2/3 x + 1 = 0

Solution

(i) a = 2, b = 7 and c = 3

Discriminant (D) = b² – 4ac

= (7)² – 4 × 2 × 3

= 49 – 48

= 1

∴ Roots are real and unequal

(ii) a = 3, b = – 2√6 and c = 2

Discriminant (D) = b² – 4ac

= (- 2√6)² – 4 × 3 × 2

= 48 – 48

= 0

∴ Roots are real and equal

(iii) a = 2, b = – 7 and c = 9

Discriminant (D) = (- 7)² – 4 × 2 × 9

= 49 – 72

= -23

∴ Roots are unreal and unequal

(iv) a = 5\over3, b = – 2\over3 and c = 1

Discriminant (D) = b² – 4ac

= (- 2\over3)² – 4 × 5\over3 × 1

= 4\over920\over3

= 4 - 60\over3

= – 56\over3

Question 2

By calculating, let us write the value(s) of k for which each of the following quadratic equations has real and equal roots —

(i) 49x² + kx + 1 = 0

Solution

Here, a = 49, b = k, and c = 1.

Discriminant (D) = k² – 4 × 49 × 1

D = k² – 196

For real and equal roots, D = 0.

k² – 196 = 0

k² = 196

k = ± 14

Thus, k = 14 or k = -14.

(ii) 3x² – 5x + 2k = 0

Solution

Here, a = 3, b = -5, and c = 2k.

Discriminant (D) = (-5)² – 4 × 3 × 2k

D = 25 – 24k

For real and equal roots, D = 0.

25 – 24k = 0

24k = 25

k = 25/24

Thus, k = 25/24.

(iii) 9x² – 24x + k = 0

Solution

Here, a = 9, b = -24, and c = k.

Discriminant (D) = (-24)² – 4 × 9 × k

D = 576 – 36k

For real and equal roots, D = 0.

576 – 36k = 0

36k = 576

k = 576/36 = 16

Thus, k = 16.

(iv) 2x² + 3x + k = 0

Solution

Here, a = 2, b = 3, and c = k.

Discriminant (D) = (3)² – 4 × 2 × k

D = 9 – 8k

For real and equal roots, D = 0.

9 – 8k = 0

8k = 9

k = 9/8

Thus, k = 9/8.

(v) x² – 2(5 + 2k)x + 3(7 + 10k) = 0

Solution

x² – 2(5 + 2k)x + 3(7 + 10k) = 0

x² – 2(5 + 2k)x + (21 + 30k) = 0

Thus, a = 1, b = -2(5 + 2k), and c = 21 + 30k.

Discriminant (D) = [-2(5 + 2k)]² – 4 × 1 × (21 + 30k)

D = [2(5 + 2k)]² – 4 × (21 + 30k)

D = 4(5 + 2k)² – 4(21 + 30k)

D = 4[(25 + 20k + 4k²) – (21 + 30k)]

D = 4(25 + 20k + 4k² – 21 – 30k)

D = 4(4 – 10k + 4k²)

D = 16 – 40k + 16k²

For real and equal roots, D = 0.

16 – 40k + 16k² = 0

Dividing the equation by 8:

2k² – 5k + 2 = 0

Solving the quadratic equation:

k = [-(-5) ± √((-5)² – 4 × 2 × 2)] / (2 × 2)

k = [5 ± √(25 – 16)] / 4

k = [5 ± √9] / 4

k = [5 ± 3] / 4

Thus, k = (5 + 3)/4 = 2 or k = (5 – 3)/4 = 1/2

Thus, k = 2 or k = 1/2.

(vi) (3k + 1)x² + 2(k + 1)x + k = 0

Solution

Here, a = 3k + 1, b = 2(k + 1), and c = k.

Discriminant (D) = [2(k + 1)]² – 4 × (3k + 1) × k

D = 4(k + 1)² – 4k(3k + 1)

Expanding the terms:

D = 4(k² + 2k + 1) – 4k(3k + 1)

D = 4k² + 8k + 4 – 12k² – 4k

D = -8k² + 4k + 4

For real and equal roots, D = 0.

-8k² + 4k + 4 = 0

Dividing by -4:

2k² – k – 1 = 0

Solving the quadratic equation:

k = [-(-1) ± √((-1)² – 4 × 2 × (-1))] / (2 × 2)

k = [1 ± √(1 + 8)] / 4

k = [1 ± √9] / 4

k = [1 ± 3] / 4

Thus, k = (1 + 3)/4 = 1 or k = (1 – 3)/4 = -1/2

Thus, k = 1 or k = -1/2.

Question 3

Let us form the quadratic equations from two roots given below —

(i) 4, 2

Solution

x² – (sum of the roots) x + (product of the roots) = 0

or, x² – (4 + 2) x + 4 × 2 = 0

or, x² – 6x + 8 = 0

(ii) -4, -3

Solution

x² – (sum of the roots) x + (product of the roots) = 0

or, x² – (-4 – 2) x + (-4) (-2) = 0

or, x² + 7x + 12 = 0

(iii) -4, 3

Solution

x² – (sum of the roots) x + (product of the roots) = 0

or, x² – (-4 + 3) x + (-4) × 3 = 0

or, x² + x – 12 = 0

(iv) 5, -3

Solution

x² – (sum of the roots) x + (product of the roots) = 0

or, x² – (5 – 3) x + (5) × (-3) = 0

or, x² – 2x – 15 = 0

Question 4

Find m for which the two roots of the quadratic equation 4x² + 4(3m – 1)x + (m + 7) = 0 are reciprocal to each other.

Solution

a = 4, b = 4(3m – 1), c = m + 7

Let the roots be α and 1/α

Product of root = c/a

or, α × 1/α = (m + 7)/4

or, 1 = (m + 7)/4

or, m + 7 = 4

or, m = – 3

Question 5

If two roots of the quadratic equation (b – c)x² + (c – a)x + (a – b) = 0 are equal, then let us prove that, 2b = a + c.

Solution

a = (b – c), b = (c – a), and c = (a – b)

Since the roots are equal, the discriminant must be 0

⇒ (c – a)² – 4(b – c)(a – b) = 0

⇒ (c² – 2ac + a²) – 4[ba – b² – ca + bc] = 0

⇒ c² – 2ac + a² – 4ba + 4b² + 4ca – 4bc = 0

⇒ a² + (-2b)² + c² – 4ba – 4bc + 2ca = 0

⇒ (a – 2b + c)² = 0

⇒ a – 2b + c = 0

⇒ 2b = a + c

Question 6

If two roots of the quadratic equation (a² + b²)x² – 2(ac + bd)x + (c² + d²) = 0 are equal, then let us prove that, a/b = c/d.

Solution

D = b² – 4ac

or, [-2(ac + bd)]² – 4(a² + b²)(c² + d²) = 0

or, 4[(ac + bd)² – (a² + b²)(c² + d²)] = 0

or, (ac)² + 2abcd + (bd)² – [(a²)(c²) + (a²)(d²) + (b²)(c²) + (b²)(d²)] = 0

or, (ac)² + 2abcd + (bd)² – (ac)² – (ad)² – (bc)² – (bd)² = 0

or, 2abcd – (ad)² – (bc)² = 0

or, (ad)² + (bc)² – 2abcd = 0

or, (ad)² + (bc)² – 2(ad)(bc) = 0

or, (ad – bc)² = 0

or, ad – bc = 0

or, ad = bc

or, a/b = c/d (Hence proved)

Question 7

Let us prove that, the quadratic equation 2(a² + b²)x² + 2(a + b)x + 1 = 0 has no real root, if a ≠ b.

Solution

Here, A = 2(a² + b²), B = 2(a + b), and C = 1.

D = B² – 4AC

or, D = [2(a + b)]² – 4 × 2(a² + b²) × 1

or, D = 4(a² + 2ab + b²) – 8(a² + b²)

or, D = 4a² + 8ab + 4b² – 8a² – 8b²

or, D = -4a² – 4b² + 8ab

or, D = -4(a² + b² – 2ab)

or, D = -4(a – b)²

For real roots, we need D ≥ 0. However, since D = -4(a – b)², this expression will always be ≤ 0. In particular:

  • If a ≠ b, then (a – b)² > 0, so D < 0.
  • If D < 0, the quadratic equation has no real roots.

Therefore, the quadratic equation 2(a² + b²)x² + 2(a + b)x + 1 = 0 has no real roots when a ≠ b.

Question 8

If two roots of the quadratic equation 5x² + 2x – 3 = 0 are α and β, then let us determine the value of:

(i) α² + β²

(ii) α³ + β³

(iii) 1/α + 1/β

(iv) α²/β + β²/α

Solution

Sum of roots (α + β) = –2\over5

Product of roots (α × β) = –3\over5

(i) α² + β² = (α + β)² – 2 × α × β

= (- 2\over5)² – 2 (-3\over5)

= 4\over25 + 6\over5

= 34\over25

(ii) α³ + β³ = (α + β)³ – 3αβ(α + β)

= (- 2\over5)³ – 3(-3\over5)(- 2\over5)

= – 8\over12518\over25

= -8 - 90\over125

= –98\over125

(iii) 1\over α + 1\over β = α + β\over αβ

= - \frac{2}{5} \over-\frac{3}{5}

= \frac{2}{3}

(iv) α²\over β + β²\over α = α³ + β³\over αβ

= - \frac{98}{125}\over - \frac{3}{5}

= \frac{98}{125} × \frac{5}{3}

= \frac{294}{25}

Was this helpful ?

Close Menu
error: Content is protected !! 💀